Metagenomic Exploration Uncovers Several Novel ‘Candidatus’ Species Involved in Acetate Metabolism in High‐Ammonia Thermophilic Biogas Processes - George B. Cheng; Erik Bongcam‐Rudloff; Anna Schnürer (Microbial Biotechnology)
ABSTRACT Biogas reactors operating at elevated ammonia levels are commonly susceptible to process disturbances, further augmented at thermophilic temperatures. The major cause is assumed to be linked to inhibition followed by an imbalance between different functional microbial groups, centred around the last two steps of the anaerobic digestion, involving acetogens, syntrophic acetate oxidisers (SAOB) and methanogens. Acetogens are key contributors to reactor efficiency, acting as the crucial link between the hydrolysis and fermentation steps and the final methanogenesis step. Their major product is acetate, at high ammonia levels further converted by SAOB and hydrogenotrophic methanogens to biogas. Even though these functionally different processes are well recognised, less is known about the responsible organism at elevated temperature and ammonia conditions. The main aim of this study was to garner insights into the penultimate stages in three thermophilic reactors (52°C) operated under high ammonia levels (FAN 0.7–1.0 g/L; TAN 3.6–4.4 g/L). The primary objective was to identify potential acetogens and SAOBs. Metagenomic data from the three reactors were analysed for the reductive acetyl‐CoA pathway (Wood–Ljungdahl Pathway) and glycine synthase reductase pathway. The results revealed a lack of true acetogens but uncovered three potential SAOB candidates that harbour the WLP, ‘Candidatus Thermodarwinisyntropha acetovorans’, ‘Candidatus Thermosyntrophaceticus schinkii’, ‘Candidatus Thermotepidanaerobacter aceticum’, and a potential lipid‐degrader ‘Candidatus Thermosyntrophomonas ammoiaca’.